ABA-mediated modulation of elevated CO2 on stomatal response to drought. (August 2020) - Li, Shenglan; Li, Xiangnan; Wei, Zhenhua; Liu, Fulai
Abstract : Elevated atmospheric CO2 concentration ( e [CO2 ]) and soil water deficits have substantial effect on stomatal morphology and movement that regulate plant water relations and plant growth. e [CO2 ] could alleviate the impact of drought stress, thus contributing to crop yield. Xylem-borne abscisic acid (ABA) plays a crucial role in regulating stomatal aperture serving as first line of defence against drought; whereas e [CO2 ] may disrupt this fundamental drought adaptation mechanism by delaying the stomatal response to soil drying. We review the state-of-the-art knowledge on stomatal response to drought stress at e [CO2 ] and discuss the role of ABA in mediating these responses.